2010
DOI: 10.1149/1.3489262
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel and Solid-State Synthesis and Property Study of La[sub 2−x]Sr[sub x]NiO[sub 4] (x≤0.8)

Abstract: In this study, sol–gel synthesis conditions for the formation of La2−xSrxNiO4 ( x=0 , 0.2, 0.4, 0.6, and 0.8) compounds were investigated. Effects of Sr substitution on A-site on the properties of the compounds were studied using Fourier transform IR spectroscopy, X-ray diffractometry, scanning electron microscopy, and electrical and thermal analyses. A simple sol–gel preparation process was successfully developed at room temperature using water as the solvent in the presence of ethanolamine as the directing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The activation energy for D* was found to be 0.60 eV ( 19 and lower than that with no Sr substitution (Ea = 0.85 eV). 11 Although, D* and k* of La 1.2 Sr0. 19,23 However, the k* value do not follow the same trend at 800°C.…”
Section: Oxygen Diffusion and Surface Exchange Coefficientsmentioning
confidence: 96%
See 3 more Smart Citations
“…The activation energy for D* was found to be 0.60 eV ( 19 and lower than that with no Sr substitution (Ea = 0.85 eV). 11 Although, D* and k* of La 1.2 Sr0. 19,23 However, the k* value do not follow the same trend at 800°C.…”
Section: Oxygen Diffusion and Surface Exchange Coefficientsmentioning
confidence: 96%
“…[5][6][7][8] Ruddlesden-Popper structure with the general formula A n+1 MnO 3n+1 (n=1,2,3,…) is a structure that comprised of ABO 3 perovskite layers, alternating with AO rock-salt layers, stacking along the c axis. 4,11 The La 2 NiO 4+δ structure is made up of sheets of (NiO 6 ) corner sharing octahedra, interleaved with La 2 O 2 layers in which the additional oxygen could be localized. Therefore, these oxygen excess materials caught a lot of interest as cathodes for SOFC applications due to their potentially high oxygen transport property.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available literature data show that the electrical conductivity of (La 1Àx Sr x ) 2 NiO 4 AE d ceramics under oxidizing conditions at temperatures below 1000 8Ct ends to increasew ith Sr content in the range 0 < x < 0.5. [1,2,38,41,43,46,47] Skinner and Kilner [6,7] reported that the substitution of 5-10 at %o fL ab yS rd ecreases oxygen tracer diffusion coefficients at 640-840 8Cb ya lmost 1-2 orders of magnitude in correlation with the decreasing concentration of mobile oxygen interstitials. In agreement with that, Li et al [48,49] demonstrated that Sr substitution results in ad ecrease of oxygen permeation fluxes through (La 1Àx Sr x ) 2 NiO 4 AE d (x = 0.05-0.10) ceramic membranes and the oxygen self-diffusion coefficient in these nickelates.…”
Section: Introductionmentioning
confidence: 99%